SURVIVING A CRISIS: META SYNTHESIS OF CRISIS COMMUNICATION STRATEGIES AND BUSINESS-TO-BUSINESS (B2B) ENTERPRISE MARKETING COMMUNICATIONS - Alfridho Yuliananda; Ummanah Ummanah (Jurnal Ekonomi, 2023)
The purpose of this research is to determine the most effective crisis communication and marketing communication strategies for B2B companies dealing with the effects of the Covid-19 pandemic. The post-positivism paradigm was used in this study using the aggregation meta-synthesis method. According to the findings of this meta-synthesis study, the power of social networks, collaboration and partnerships, and the beginning of a transition to a digital communication system becomes an effective means of carrying out crisis management in uncertain conditions. B2B companies that are already capable of implementing this crisis communication strategy can concurrently or gradually begin implementing a marketing communication strategy through online marketing, virtual/online exhibitions, social media marketing, and price discounting or price reductions. All of these processes must be carried out due to the limitations of social meetings/interactions between individuals in the Covid-19 crisis situation.